2013
DOI: 10.5762/kais.2013.14.8.3850
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation on the oral health promotion program effect from some part of community child center

Abstract: This study aims to examine the effect of the program by identifying changes in oral health behaviors, oral health knowledge, the Patient Hygiene Performance(PHP) index and others after performing oral health promotion program on children in community children's centers to develop persistent and more effective program. The final analysis subjects were 27 children. According to the examination results of dental plaque score, the PHP index score was reduced from 3.42 to 2.43 before and six month after the tooth b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…Eom et al 27) also reported that repeated individual toothbrushing instruction changed oral health knowledge, perceptions and behaviors, and significantly improved the dental plaque index in their study. Repeated individual toothbrushing instruction was also effective for children in a previous study 28) . They reported that the method of instruction improved children's knowledge about dental caries motivated their interest of self-care for oral health promotion, and increased their daily toothbrushing frequency.…”
Section: Discussionmentioning
confidence: 76%
“…Eom et al 27) also reported that repeated individual toothbrushing instruction changed oral health knowledge, perceptions and behaviors, and significantly improved the dental plaque index in their study. Repeated individual toothbrushing instruction was also effective for children in a previous study 28) . They reported that the method of instruction improved children's knowledge about dental caries motivated their interest of self-care for oral health promotion, and increased their daily toothbrushing frequency.…”
Section: Discussionmentioning
confidence: 76%
“…Teachers are aware of the need for oral health education for children, but it has been found that there are not enough educational aids and media, and the oral health education-related programs conducted in childcare centers are insufficient (Choi et al 2013). In previous studies, although there were differences in the effects on oral health behaviors depending on the educational method and medium, oral health education using appropriate educational media had positive changes in dental plaque control and oral health behavior (Lee and Choi 2017;Sharififard et al 2020).…”
Section: Introductionmentioning
confidence: 99%